Implementation of Basic Training (Latsar) for Candidates for Civil (CPNS) Bleended Learning Pattern in Kerinci District - Lailatul Isnaini; Masfifah Masfifah; Istikomah Istikomah (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: Aims to find, study, and describe the implementation of basic training for prospective civil servants using a blended learning pattern from the aspects of communication, resources, and infrastructure. Background Problems: Find factors that become obstacles and supports in implementing basic training for prospective civil servants. (CPNS) Blended Learning pattern in Kerinci District in. Research Methods: Qualitative method, analyzing the activities of CPNS Basic Training in Kerinci Regency. Data mining is sourced from primary data and secondary data. Preliminary data in words, attitudes, or actions were obtained through interviews, and direct and indirect observations were obtained from the primary source, the organizing team, widyaiswara, and Latsar participants. Secondary data is obtained through documents, previous studies, books, meeting agendas, and those related to the problem being researched. Finding/Results: Research shows that implementing blended learning CPNS basic training in Kerinci Regency is effective. Communication and coordination of the performance of the latsar are pretty good. Human resources (organizers, teaching staff, and participants) can carry out their respective duties well. Facilities and infrastructure to support the smooth running of CPNS latsar activities, both when distance learning and classical learning, are exemplary. The output in the Latsar CPNS activity in Kerinci Regency, all participants (109 people) successfully passed. Conclusion: The internet network is not evenly distributed, so distance learning activities are less effective. Meanwhile, supporters of the smooth implementation of the Kerinci CPNS latsar include budget support, competent teaching staff (WI), and excellent cooperation.